Plasmon-induced photoelectrochemical water oxidation enabled by in situ layer-by-layer construction of cascade charge transfer channel in multilayered photoanode. Issue 48 (28th November 2018) - Zeng, Zhiping; Li, Tao; Li, Yu-Bing; Dai, Xiao-Cheng; Huang, Ming-Hui; He, Yunhui; Xiao, Guangcan; Xiao, Fang-Xing
Abstract : Cascade charge transfer between graphene quantum dots and Ag nanocrystals in photoelectrochemical water splitting was finely regulated by layer-by-layer (LbL) assembly. Abstract : Tunable and efficacious modulation of photo-induced charge carrier separation and transfer in photoelectrochemical (PEC) cell for solar water splitting constitute a central challenge. Herein, high-efficiency plasmon-induced hot carriers transfer channel has been rationally and progressively constructed by judicious layer-by-layer assembly of graphene quantum dots (GQDs) and plasmonic metal nanocrystals (Ag NCs) on the one-dimensional semiconductor (TiO2 nanorods arrays, TiO2 NRs) framework, resulting in a well-defined spatially multilayered photoanode. The unique and alternate integration of GQDs with Ag NCs on the TiO2 NRs is closely associated with charge transfer behaviors. It was unveiled that Ag NCs in situ integrated in the multilayered film enable hot electron generation, and simultaneously play a crucial role in finely relaying electron transfer from GQDs to TiO2 . This gives rise to significantly enhanced solar-powered PEC water splitting performances of TiO2 NRs@Ag@GQDs ternary multilayered heterostructure, which far surpasses the corresponding binary and single counterparts. Consequently, intrinsic correlation of metal NCs with GQDs in terms of charge transport was for the first time clarified.